The Conceptual Model of Community Learning Center (PKBM) in Indonesia and Community Cultural Learning Center (Kominkan) in Japan - Yunus Lutfiansyah, Dadang; Hufad, Achmad; ., Purnomo (International Journal of Engineering and Technology, 2018)
This study explored the model of public education services conducted in two countries, namely Japan and Indonesia, particularly in understanding the objective condition of society between the two countries (background/history), then the conceptual model and implementation of public education model in industrial society in Indonesia and Japan. The concepts used in this research were lifelong learning, community-based education, and community learning centers. This research used descriptive study method with a qualitative approach. The data collection techniques used included interview techniques, observation, literature study, and documentation study. The results showed that; 1) the objective condition/Indonesian society during the establishment of PKBM in 1997 was in the economic crisis/monetary crisis. The infrastructure and education system were relatively existing and running. Institutionally, PKBM was separated from the existence of formal education (in this case, school); moreover, the orientation of the program services tended to be on the basic fulfillment. As for Japan, in post-World War II, the condition of infrastructure and social system was destroyed. At the beginning, school and kominkan were side by side by and the service orientation was holistically integrative and for the leisure time 2) the conceptual model of community education in the industrial society was based on the principle of community-based learning, Education for All as well as Education for Sustainable Development (ESD), and the cultural values and local wisdom. 3) The implementation of community education model in the industrial society developed by PKBM was through a) The Input Program (raw input, instrumental input, environmental input, process, output, other input, and impact), b) Learning Process and c) Output of learning. As in Kominkan in Japan, it adhered to the three main characteristics which were the information centers, the centers of participation and self-actualization which were open to all ages and circles as well as a place that guaranteed freedom and equal rights, free services, had an autonomy as a learning and cultural institution, had staff, was affordable (accessibility) with adequate facilities and high community participation.Â Â